2021
DOI: 10.2337/db20-1281
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Molecular Signatures of Clinical Clusters in People With Type 2 Diabetes: An IMI-RHAPSODY Study

Abstract: Type 2 diabetes is a multifactorial disease with multiple underlying aetiologies. To address this heterogeneity, investigators of a previous study clustered people with diabetes according to five diabetes subtypes. The aim of the current study is to investigate the etiology of these clusters by comparing their molecular signatures. In three independent cohorts, in total 15,940 individuals were clustered based on five clinical characteristics. In a subset, genetic (N = 12,828), metabolomic (N = 2,945), lipidomi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 43 publications
4
29
0
Order By: Relevance
“…Higher SIRD-MRS and MARD-MRS were associated with an increased risk of developing CVD and CKD, whereas a higher MOD-MRS was associated with lower risk for developing these two complications. Our results are supported by previous studies, where patients with SIRD had a higher risk of CKD and patients with MOD had a lower risk of CKD and coronary events ( 4 , 11 ). In the current study, we also found that the associations between patients with MOD and those with MARD and the risk for CVD and CKD were similar to the associations observed for MOD-MRS and MARD-MRS. On the other hand, SIRD-MRS and SIDD-MRS were able to predict CVD and/or CKD, whereas patients with SIRD and those with SIDD were not associated with the risk of these diseases, suggesting a potentially better ability of these MRSs on predicting complications compared with the T2D subgroups.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Higher SIRD-MRS and MARD-MRS were associated with an increased risk of developing CVD and CKD, whereas a higher MOD-MRS was associated with lower risk for developing these two complications. Our results are supported by previous studies, where patients with SIRD had a higher risk of CKD and patients with MOD had a lower risk of CKD and coronary events ( 4 , 11 ). In the current study, we also found that the associations between patients with MOD and those with MARD and the risk for CVD and CKD were similar to the associations observed for MOD-MRS and MARD-MRS. On the other hand, SIRD-MRS and SIDD-MRS were able to predict CVD and/or CKD, whereas patients with SIRD and those with SIDD were not associated with the risk of these diseases, suggesting a potentially better ability of these MRSs on predicting complications compared with the T2D subgroups.…”
Section: Discussionsupporting
confidence: 92%
“…Our group and others have found epigenetic differences in tissues from patients with T2D versus control subjects ( 11 15 ), demonstrating that epigenetic mechanisms contribute to the pathogenesis of T2D. Moreover, there has been an increasing interest in identifying blood-based epigenetic biomarkers for risk assessment in patients with diabetes.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…At present, the only study integrating genetic, metabolomic, lipidomic and proteomic data to compare diabetes subtypes was based on different clustering variables (age, BMI, HbA 1c , HDL-cholesterol, and random or fasting Cpeptide). SIRD showed the most distinct molecular signature, mostly related to insulin resistance, lipids and inflammation [50].…”
Section: Gada Negativementioning
confidence: 99%
“…These might include measures of adiposity, disease duration, beta cell function or insulin action: in this regard, a basal or stimulated C-peptide holds singular promise. In addition, agnostic explorations for such biomarkers as can be assessed by global metabolomic profiling are of intense interest [22][23][24].…”
Section: Robust and Reproducible Metabolic Or Phenotypic Biomarkersmentioning
confidence: 99%